SYNTHESIS of 3.4-METHYLENEDIOXYPHENYL-2-PROPANONE from SAFROLE - Hanoch J Sohilait; Hardjono Sastrohamidjojo; Sabirin Matsjeh; J Stuart Grossert (Universitas Gadjah Mada, 2001)
The Synthesis of 3.4-methylenedioxyphenyl-2-propanone from safrole has been achieved through conversion of allyl group to secondary alcohol, followed by oxidation with pyridinium chlorochromate(PCC). The secondary alcohol has been achieved by two methods. The first method was formic acid adition reaction, followed by hydrolysis in aqueous ethanolic solution of potassium hydroxide. The second method was the oxymercuration-demercuration reaction of safrole. The addition reaction of safrole with formic acid yield safrylformate (34,70%). The hydrolysis of safrylformate with 3M KOH produced safrylalchohol (73,29%). The oxymercuration-demercuration reaction of safrole with Hg(OAc)2-NaBH4 gave (74,37%) of safrylalcohol. The oxidation of safryalcohol with PCC gave 3.4-methylenedioxyphenyl-2-propanone as a main target in 71,83%. The structure elucidations of these products were analyzed by FTIR , 1H-NMR, 13C-NMR and MS.